OP0047 Expression of Heat Shock Protein 90 in Muscle Tissue and Plasma Is Increased in Idiopathic Inflammatory Myopathies and Correlates with Disease Activity, Skeletal Muscle, Heart and Lung Involvement. (15th July 2016) - Storkanova, H.; Krystufkova, O.; Klein, M.; Mann, H.; Vernerova, L.; Spiritovic, M.; Zamecnik, J.; Pavelka, K.; Senolt, L.; Vencovsky, J.; Tomcik, M.
Abstract : Background: Heat shock proteins (Hsps) are chaperones playing important roles in skeletal muscle physiology, adaptation to exercise/stress, and activation of inflammatory cells. Objectives: To assess Hsp90 expression in muscle biopsies and plasma of patients with idiopathic inflammatory myopathies (IIM) and to characterize its association with IIM-related features. Methods: Total of 277 patients with IIM (198 females, 79 males; mean age 54.8; disease duration 4.1 years; dermatomyositis (DM, 104)/polymyositis (PM, 104)/cancer associated myositis (CAM, 42)/ necrotizing myopathy (IMNM, 27)) and 100 age-/sex-matched healthy individuals were included in plasma analysis and 50 muscle biopsy samples were stained for Hsp90 (PM-10, DM-10, IMNM-10, myodystrophy-10, myasthenia gravis-10). Patients with PM/DM fulfilled Bohan and Peter criteria and CAM was defined as cancer within 3 years of IIM diagnosis. Plasma Hsp90 was measured by ELISA (eBioscience, Vienna, Austria). Clinical disease circumstances were evaluated by Myositis Disease Activity Assessment (MYOACT), Myositis Intention to Treat Index (MITAX), Myositis Damage Index (MDI), physician and patient global activity using VAS and manual muscle testing (MMT8). CK, LD, ALT, AST and CRP were analyzed by routine techniques and IIM-specific autoantibodies by in-line blot and immunoprecipitation. Data are presented as median. Results: In muscle biopsies Hsp90 expression was higher in IIM than in myodystrophy (myasthenia gravis used as another control was negative). Increased Hsp90 was detected in perifascicular degenerating and regenerating fibers, inflammatory cells (DM, PM), and necrotic and regenerating fibers (IMNM). Plasma Hsp90 levels were increased in IIM patients compared to healthy controls (20.2 vs. 9.2 ng/ml, p<0.0001), and in individual subgroups of IIM vs. healthy controls (PM: 19.4, DM: 22.4, CAM: 19.1, IMNM: 19.6 ng/ml, p<0.0001 for all). Hsp90 levels in all patients positively correlated with LD and AST (r=0.551, p<0.0001; r=0.372, p<0.0001, respectively), and there was a trend towards correlation with CK (r=0.111, p=0.068). Increased Hsp90 was associated with decreased MMT8 values (r=-0.136, p=0.029), in particular in proximal muscles. Hsp90 positively correlated with patient and doctor disease activity (r=0.222, p=0.0004; r=0.217, p=0.0005, respectively), pulmonary and muscle disease activity (r=0.201, p=0.001; r=0.146, p=0.018, respectively), MITAX and MYOACT (r=0.175, p=0.005; r=0.159, p=0.012, respectively), and with MDI extent/severity (r=0.215, p=0.003; r=0.120, p=0.041, respectively). Higher Hsp90 was found in patients with interstitial lung disease, cardiac involvement and dysphagia (25.4 vs. 18.9, p=0.004; 27.5 vs. 19.3, p=0.004; 25.0 vs. 18.2, p=0.018, respectively). Conclusions: We demonstrate increased Hsp90 expression in IIM muscle biopsy samples, specifically in inflammatory cells, degenerating, regenerating and/or necrotic fibers. Increased Hsp90 plasma levels in IIM patients are associated with disease activity and damage, and with the involvement of proximal skeletal muscles, heart and lungs. Acknowledgement: Supported by BT Cure, MHCR-23728. Disclosure of Interest: None declared